The ion sensitive field effect transistor (ISFET) pH electrode: a new sensor for long term ambulatory pH monitoring. Issue 3 (March 1991) - Duroux, P; Emde, C; Bauerfeind, P; Francis, C; Grisel, A; Thybaud, L; Arstrong, D; Depeursinge, C; Blum, A L
Abstract : Intraluminal pH monitoring in man should be performed with disposable multichannel assemblies that allow recordings at multiple sites and prevent transmission of infection. Currently available glass electrodes are unsuitable for this purpose because of their size and price. We have thus constructed and tested a small, combined ion sensitive field effect transistor (ISFET) pH electrode incorporating an integral reference electrode. In vitro studies showed that both ISFET and glass electrodes (440-M4, Ingold, Switzerland) have a linear response over the pH range 1.3-8.0 and that they are comparable with regard to response time and 24 hour drift. Twenty one hour intragastric pH recordings were performed simultaneously in eight healthy volunteers using a glass electrode and an ISFET electrode, placed no more than 2 mm apart in a combined assembly. This was located in the gastric corpus under fluoroscopic control. The 21 hour pH curves recorded by each electrode type showed identical patterns: an early morning rise in pH with three meal-associated pH peaks lasting for about two to three hours. The means of the 21 hour pH medians were 2.09 and 2.07 as measured by the glass and the ISFET electrodes respectively. Thus, ISFETs are suitable for the construction of inexpensive and hence disposable multichannel pH monitoring assemblies of small diameter. Provided that they can be produced in large numbers with appropriate technical support, ISFETs have the potential to replace glass electrodes for long term monitoring of gastrointestinal luminal acidity.